تحليل وتصميم الهوائيات الشرائحية المطبوعة باستخدام نظرية Galerkin - السموءل صالح; معين يونس; أمجد سعيدي (Tishreen University, 2019)
يقدم  هذا البحث نتائج تحليل وتصميم  الهوائيات الشرائحية المطبوعة باستخدام نظرية Galerkin . تم في هذا البحث استنتاج المعادلات الرياضية الممثلة لنظرية Galerkin التي تهدف إلى دراسة الانقطاع في دليل الموجة، وحساب الممانعة المكافئة لهذا الانقطاع من أجل استخدامها في تحليل وتصميم الهوائيات الشرائحية المطبوعة . إن استخدام نظرية Galerkin في تصميم  الهوائي الشرائحي مكننا من تحديد تردد الهوائي الشرائحي بدقة وزمن قياس مناسبين مقارنة بباقي طرق تصميم الهوائي الشرائحي، ومكننا أيضاً من تحديد ورسم القسم التخيلي والحقيقي لممانعة دخل الهوائي الشرائحي، ثم تمت دراسة علاقة تردد الهوائي الشرائحي  بأبعاده، وملاحظة تغير تردد الهوائي الشرائحي وفقاً لأبعاده، وأيضاً دراسة علاقة تردد عمل الهوائي مع عدد الأنماط اللازمة لتصميمه، ودراسة أثر تغير السماحية الكهربائية للمادة العازلة المكونة لبنية الهوائي الشرائحي على الخواص الإشعاعية  لهذا الهوائي. This search describes results of analysis and design of Microstrip Printed Antennas using Galerkin theory. In this search, we have concluded the mathematical equations that represent Galerkin theory, which aims to study the cut in a waveguide, and calculate its equivalent impedance, to analyze and design microstrip antennas. Using Galerkin theory for designing enabled us to calculate the microstrip antenna frequency, in a precise and fast way, comparing with other ways of designing. It also enabled us to determine and plot the real and imaginary part of the input impedance of the antenna. After that, we studied the relationship between the antenna frequency and its dimensions, and how frequency changes according to dimensions, and also the relationship between frequency and number of modes needed to design the antenna, and how changing the electrical permittivity of the isolator in the antenna affects its radiation characteristics.